VP48 The Costs And Cost-Effectiveness Of Bacillus Calmette-Guérin (BCG) Vaccination In Estonia. (12th January 2018) - Reile, Rainer; Närska, Margit; Pehme, Lea; Võrno, Triin
Abstract : INTRODUCTION: Many countries that have used Bacillus Calmette-Guérin (BCG) vaccine against tuberculosis (TB) have switched from universal vaccination of infants and children to selective vaccination, or discontinued with vaccination at all. The aim of the study is to assess the costs and cost-effectiveness of BCG vaccination in Estonia. METHODS: A Markov cohort model and budget impact analysis were used to compare the current, universal BCG vaccination to selective and non-vaccination strategies. The epidemiological and economic impact of BCG vaccination were estimated for the period 2018–2032 following the hypothetical change in the vaccination policy in 2018. The results were presented as the cost per case of TB adverted, changes in the occurrence of TB and yearly (undiscounted) costs associated with vaccination and TB treatment. RESULTS: In a cohort of 13, 500 infants over a time-period of 15 years Estonian universal BCG vaccination prevents around two TB cases compared to selective or non-vaccination strategies. The cost per one TB case averted for the universal strategy compared to non-vaccination strategy was EUR12, 234 (EUR4, 059–28, 748 in sensitivity analysis) and compared to selective vaccination EUR3, 847 (EUR504–10, 568). The number of TB cases in 0–14-year old children in 2032 was estimated to be 1.3 for universal vaccination, 2.7 for selective and 2.9 for non-vaccination strategy. The total costs of vaccination and TB treatment in 2032 were estimated to be EUR23, 764, EUR16, 459 and EUR7, 553 respectively. CONCLUSIONS: The cost per case of TB averted is dependent on vaccine efficacy, and is high compared with the cost of treating one case of TB. At the same time, the total costs of BCG vaccination and TB treatment are marginal compared to other vaccination programs used in Estonia. Despite the limited budget impact, several organizational challenges need to be addressed if the universal program is replaced with selective BCG vaccination.